2018
DOI: 10.1101/454439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A simple Dot Blot Assay for population scale screening of DNA methylation

Abstract: The study of epigenetic changes in natural and experimental populations has increased the need to find a cost-effective and high throughput method to analyze multiple samples to effectuate a population-wide screening to study epigenetic changes triggered by biotic or abiotic stress. One of the most studied epigenetic marks is global DNA methylation, its measurement is used as a first step to differentiate methylation between individuals. There is a wide range of methods designed to detect genome-wide 5 methylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…For this reason, this method determines only large variations in DNA methylation, and therefore, it is only suitable for the rough estimation of DNA methylation. However, the dot blot assay is a suitable method to perform a large‐scale screening of global DNA methylation, since it requires a smaller amount of DNA, is less expensive, and allows many more samples to be analyzed in parallel (Luviano et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, this method determines only large variations in DNA methylation, and therefore, it is only suitable for the rough estimation of DNA methylation. However, the dot blot assay is a suitable method to perform a large‐scale screening of global DNA methylation, since it requires a smaller amount of DNA, is less expensive, and allows many more samples to be analyzed in parallel (Luviano et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…New DNMTi influence global DNA methylation in vivo over two consecutive generations (multigenerational effect) Using a newly developed population epigenetics screening method that delivered results comparably to ELISA (Supplementary file 2, Figure S4 and S5) but at much lower costs (Luviano et al 2018) we showed that, in the F0 generation, zebularine did not produce a statistically significant difference in 5mC % compared to the control group (W=383, p=0.32). However, 5mC % was significantly different in the groups treated with Flv1 (W=365 p<0.0001) and Flv2 (W=445, p<0.0001) compared to control.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the densitometry of the 5mC was analyzed with the software ImageLab5.1. Detailed protocol of this method is found in our preprint (Luviano et al 2018).…”
Section: Dna Methylation Screeningmentioning
confidence: 99%
“…Using dot blot method [ 56 ], we found significant differences in the 5mC% between treatments (Kruskal–Wallis test, p < 0.001). In the F0 generation, zebularine did not produce a statistically significant difference in 5mC% compared to the control group (Dunn’s test p > 0.9).…”
Section: Resultsmentioning
confidence: 99%